Qualidade de Vida à luz do processo de Urbanização Contemporânea: análise a partir de indicadores municipais, intraurbanos e das relações estabelecidas na Região Geográfica Imediata de Araxá, MG - Souza, Josimar dos Reis de (2020)
The present study aimed to analyze the quality of life in the Immediate Geographic Region (RGI) of Araxás, Minas Gerais, in the light of the process of Contemporary Urbanization experienced in Brazil and in the World, using indicators from three scales - municipal, intra-urban and relations established between the municipalities/cities, in order to understand how the analysis at the regional level can contribute with a more complete picture of the living conditions and the levels of access of the different layers of the population to aspects related to both basic needs, as well as those related to individual satisfactions and aspirations related, above all, to consumption. The research was motivated by the understanding that the analysis of the quality of life through the use of municipal and intra-urban indicators is of paramount importance for the recognition of the reality experienced and for the identification of the existing disparities within the same urban environment. But in addition, in the context of Contemporary Urbanization, cities took on different roles, especially at the regional level, whose functions carried out by larger urban centers led to the consolidation of daily flows from other cities/municipalities, both for basic needs, also due to motivations associated with individual interests related to the search for the realization of personal aspirations linked to well-being, and in both situations the needs for displacement that alone generate aspects that permeate quality of life. Thus, it was considered that in the context evidenced, it became essential to also analyze the dependency relations established at the regional level. The three scales analyzed considered indicators of the dimensions of sanitation, housing, income, social assistance, health and education, in addition to the relationships established by the structuring of the public and private medical-hospital network, the location of technical and higher education institutions, configuration of the sector trade and services and flows related to leisure-consumption. The methodological paths perfected the stages of bibliographic research, data collection and tabulation, documentary research, field research, questionnaire application, conducting interviews, producing maps and creating figures, tables and tables. The results of the research were structured in four chapters, whose main analyzes showed the situation of the different layers of the population and the areas of the cities that need more attention by the public management; the main difficulties faced by the portion of the population that needs to travel for various reasons related to health, education and trade/services; the possible solutions to improve the conditions of these displacements; the regional configuration and the levels of access to consumption-leisure activities and the role that cities have assumed in this contemporary dynamic.